2018
DOI: 10.1001/jamainternmed.2017.7720
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cardiovascular Risk With Inhaled Long-Acting Bronchodilators in Patients With Chronic Obstructive Pulmonary Disease

Abstract: IMPORTANCEThe associations between cardiovascular disease (CVD) and inhaled long-acting β 2 -agonists (LABAs) or long-acting antimuscarinic antagonists (LAMAs) in chronic obstructive pulmonary disease (COPD) are greatly debated. Pivotal and relevant randomized clinical trials included prior LABA or LAMA users and excluded patients with baseline CVD; therefore, cardiovascular events arising from first-time LABA or LAMA use, if any, could not be observed. There is an urgent need to examine whether new use of and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
112
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(125 citation statements)
references
References 37 publications
8
112
0
2
Order By: Relevance
“…For example, individuals may initiate or intensify use of bronchodilators during an exacerbation . As these drugs stimulate sympathetic control and suppress the parasympathetic nervous system, their use may imply a short‐term increased cardiovascular risk . Similarly, exacerbations are often also treated with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, individuals may initiate or intensify use of bronchodilators during an exacerbation . As these drugs stimulate sympathetic control and suppress the parasympathetic nervous system, their use may imply a short‐term increased cardiovascular risk . Similarly, exacerbations are often also treated with antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…16 As these drugs stimulate sympathetic control and suppress the parasympathetic nervous system, their use may imply a short-term increased cardiovascular risk. 32,33 Similarly, exacerbations are often also treated with antibiotics. Although some antibiotics may increase the risk of cardiac events, 34,35 it is the site of infection more than the choice of antibiotic causing the increased risk.…”
Section: Discussionmentioning
confidence: 99%
“…In the pharmacological therapies for COPD and urinary incontinence, adverse effects and drug-drug interactions are also noted, which is consistent with recent studies. 19 As shown in Table S3, COPD patients taking Xiao Qing Long Tang are associated with alleviated airway inflammation and restored airway remodeling, 20 Log-Rank test, P = 0.0009 CHM cohort Fig. 2 Cumulative incidence of urinary incontinence after 10 years for the CHM cohort and non-CHM cohort in patients with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] These patients have a 2 to 5 times elevated risk of ischemic heart disease, cardiac arrhythmia, and heart failure. 14 Some case studies have reported LAMA and long-acting beta agonist (LABA) treatments increase the risks of cardiovascular events in COPD patients 15,16 ; however, other studies, including prospective trials, have shown no elevated risks for cardiovascular events with LAMA or LAMA/LABA combinations. [17][18][19][20] Revefenacin has not been associated with adverse cardiovascular events in 2 identical double-blind, placebo-controlled, 12-week phase 3 trials (NCT02512510, NCT02459080) 21 or in a 52-week double-blind phase 3 study (NCT02518139) 22 of patients with moderate to very severe COPD.…”
Section: Discussionmentioning
confidence: 99%